2020
DOI: 10.1111/mcn.13012
|View full text |Cite
|
Sign up to set email alerts
|

Early breastfeeding practices contribute to exclusive breastfeeding in Bangladesh, Vietnam and Ethiopia

Abstract: Limited evidence exists on the complex relationship among interventions, early initiation of breastfeeding (EIBF), prelacteal feeding and exclusive breastfeeding (EBF). We examined whether early breastfeeding practices are associated with EBF and how much improving EIBF and non‐prelacteal feeding contributes to increased prevalence of EBF. Survey data were collected in 2010 and 2014 as part of impact evaluations of Alive & Thrive (A&T) interventions to improve infant and young child feeding (IYCF) practices in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Breastfeeding prevents the introduction of potentially contaminated prelacteal foods, provides newborns with colostrum (rich in a variety of nutrients and immunoglobulins) and protects against diarrheal diseases and respiratory tract infection [ 7 , 8 , 9 , 10 , 11 , 12 ]—two leading causes of preventable under-five-years deaths in Bangladesh [ 13 ]. Numerous research from Bangladesh has identified the determinants of breastfeeding (BF) practices among mothers of all age groups [ 14 , 15 , 16 , 17 , 18 ]. However, specific studies that focus on breastfeeding practices of adolescent mothers are limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breastfeeding prevents the introduction of potentially contaminated prelacteal foods, provides newborns with colostrum (rich in a variety of nutrients and immunoglobulins) and protects against diarrheal diseases and respiratory tract infection [ 7 , 8 , 9 , 10 , 11 , 12 ]—two leading causes of preventable under-five-years deaths in Bangladesh [ 13 ]. Numerous research from Bangladesh has identified the determinants of breastfeeding (BF) practices among mothers of all age groups [ 14 , 15 , 16 , 17 , 18 ]. However, specific studies that focus on breastfeeding practices of adolescent mothers are limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, specific studies that focus on breastfeeding practices of adolescent mothers are limited. Key factors associated with appropriate breastfeeding practices among Bangladeshi mothers of all age groups included non-prelacteal feeding practices [ 15 ], a lack of intimate partner violence and/or child abuse [ 14 ], access to mass media, home birthing [ 16 ], non-caesarean birthing, and receipt of breastfeeding counselling, antenatal and postnatal care [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is an evidence-based intervention for promoting children’s health, development, and survival [ 1 , 2 , 3 , 4 , 5 , 6 ]. The provision of mother’s breastmilk to infants within one and a half hours of birth, referred to as early initiation of breastfeeding (EIBF), is associated with continued exclusive breastfeeding (EBF) at discharge and through the first 6 months of life [ 7 , 8 , 9 , 10 ]. A 2017 systematic review showed that infants who initiated breastfeeding more than 24 h after birth had a twofold greater risk of neonatal mortality compared to infants who initiated breastfeeding within one hour [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Full-text eligibility checks of the remaining 52 articles excluded 29 studies. The reasons for exclusion of studies included: 4 studies were duplicates, 42–44 1 study was cross-sectional, 45 2 studies used qualitative evaluation, 46 47 10 studies were abstracts, 48–57 4 studies were based on the design and implementation of interventions, 58–61 5 studies did not measure IYCF outcomes, 62–70 and 3 studies were based on interventions designed for different target groups 71–73 ( figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Full-text eligibility checks of the remaining 52 articles excluded 29 studies. The reasons for exclusion of studies included: 4 studies were duplicates, [42][43][44] 1 study was cross-sectional, 45 2 studies used qualitative evaluation, 46 47 10 studies were abstracts, [48][49][50][51][52][53][54][55][56][57] 4 studies were based on the design and implementation of interventions, [58][59][60][61] 5 studies did not measure IYCF outcomes, [62][63][64][65][66][67][68][69][70] and 3 studies were based on interventions designed for different target groups [71][72][73] (figure 1). Among the 23 included studies, 14 were quasiexperimental studies, [74][75][76][77][78][79][80][81][82][83][84][85][86][87] while the remaining 9 were cluster randomised trials.…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%